2012
DOI: 10.1039/c2ce06190b
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular H⋯H steric hindrance modulated aggregate packing and optoelectronic properties in 1-naphthyl, 9-anthryl end-capped styrylarylene derivatives

Abstract: The crystal structures and optoelectronic properties of the compounds 1,4-bis[2-(1-naphthyl)vinyl] benzene (BNVB), 4,4 0 -bis[2-(1-naphthyl)vinyl]biphenyl (BNVBP) and 4,4 0 -bis[2-(9-anthryl)vinyl] biphenyl (BAVBP) were studied and compared. Due to intramolecular H/H steric hindrance, BAVBP molecules adopt a twisted conformation and constructed into a three-dimensional C-H/p interacting structure. In contrast, the H/H steric hindrance is alleviated in compounds BNVB and BNVBP. Both molecules have much better p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…1d The low OFET performance of 2BFVB is possibly due to the still short p- With the improved p-conjugation length the carrier-mobility increases from 10 À6 cm 2 V À1 s À1 to 10 À3 cm 2 V À1 s À1 . 14 As shown in Fig. 6, both 2BFVB and 3BFVB can form a crystalline lm on OTS-pretreated SiO 2 at 60 C. However, the carrier-transport ability of 3BFVB is much lower than that of 2BFVB.…”
Section: Structural Investigation On the Thin Lms And Ofet Propertiesmentioning
confidence: 86%
See 2 more Smart Citations
“…1d The low OFET performance of 2BFVB is possibly due to the still short p- With the improved p-conjugation length the carrier-mobility increases from 10 À6 cm 2 V À1 s À1 to 10 À3 cm 2 V À1 s À1 . 14 As shown in Fig. 6, both 2BFVB and 3BFVB can form a crystalline lm on OTS-pretreated SiO 2 at 60 C. However, the carrier-transport ability of 3BFVB is much lower than that of 2BFVB.…”
Section: Structural Investigation On the Thin Lms And Ofet Propertiesmentioning
confidence: 86%
“…This is different from 4,4 0 -bis[2-(1-naphthyl) vinyl]benzene, which has a classical herringbone packing structure. 14 Overall, 2BFVB is a kind of 2D semiconductor.…”
Section: Single-crystal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…All the molecules exhibit distorted conformation due to the intramolecular steric hindrance. 39 The optimized geometric structure of 1 show twisted conformation with a dihedral angle of 56.63 (Fig. S17 †).…”
Section: Optical Propertiesmentioning
confidence: 99%
“…For example, Tang's group reported that the E-Z isomerization may be not involved in the AIE process of stilbene derivatives. 4 Now it is generalized that the AIE process may be dependent on many factors, such as the molecule's planarity, 1b steric hindrance, 5 intramolecular rotation, 6 or intermolecular interactions. 3 So far, most AIE studies emphasize the role of the solid-state character in the emission enhancement.…”
mentioning
confidence: 99%